COVID-19 pandemic and its impact on demographic processes (Journal of Philosophy, Culture and Political Science, 2023)
The emergence of a global pandemic and the spread of the COVID-19 virus has become the latest challenge and security threat for the political communities of the modern world. The pandemic has become truly global. For some time, governments have been quite timely in resolving issues of the spread and impact of global pandemics. However, the topic studied really raised the question of the effectiveness of the world community's counteraction to the emerging problem, which has become global in nature. The authors of the article, based on a study of a wide range of new and diverse sources and using scientific research methods, undertook an analysis of the role and impact of the COVID-19 pandemic on an international scale. The main results and conclusions of the proposed article make a certain contribution to the study and prevention of new global threats at the level of national states and their joint fight against problems. However, various studies remain to be conducted on a wide range of issues related to the global pandemic and its consequences. In this regard, the authors of the article suggest the particular relevance of the analyzed data and the situation in the world in the context of preventing global threats in a globalizing political community.Key words: pandemic, COVID-19, demography, threat, globalization.